Exploring View of Nature of Science and Technology Pre-Service Chemistry Teachers - Devita Marlina Venessa; Hernani Hernani; Heli Siti Halimatul (Journal of Science Learning, 2019)
This study aims to explore the views of pre-service chemistry teachers on the nature of science and technology. Pre-service chemistry teachers’ view of nature of science and technology (VNOST) is very important to help their students later in understanding the concepts of science. This research is the initial stage in didactical design research involving 48 pre-service chemistry teachers from Sriwijaya University. The descriptive method is used to explain the results of the analysis of pre-service chemistry teachers’ VNOST. Student views were assessed using the VNOST questionnaire, consisting of 8 questions and guided by the discourse of ionic liquid technology. Data collection uses a survey containing the views of pre-service chemistry teachers on VNOST and where each statement grouped according to three categories, namely "Realistic" (R), "Has Merit" (HM), and Naïve (N). The results showed that in general, students have the view of Has Merit (HM), or the belief that they chose is not entirely correct even though there are parts of statements that are still by the general view of science. The results of this student VNOST exploration are the basis for developing learning designs that are oriented to the realist answers of each question so that learning designs are produced based on aspects of the Nature of Science and Technology.